Exploring market potential and consumer preferences for fungus-resistant grape varieties: A discrete choice analysis in Germany - Christoph Kiefer; Gergely Szolnoki (Future Foods)
While fungus-resistant grape varieties (FRGVs) offer comprehensive sustainable benefits, their slow adoption and consumer preferences warrant investigation. Therefore, a discrete choice model for key parameters influencing consumer perceptions, including product attributes, pricing, grape variety preferences, labelling and information dissemination, was constructed based on a representative sample of 1276 wine consumers in Germany. The data were analysed using a conditional logit utility model to gain insights into the preferences and willingness to pay (WTP) of each product attribute. Due to the low level of awareness of these grape varieties, the sample was divided into two groups: a control group and an experimental group, which was conditioned prior to the study to investigate the market potential of FRGVs. The results show that the conditioned group exhibited a stronger inclination towards FRGVs, indicating an increased awareness of environmentally friendly practices. Price sensitivity was influenced by conditioning, with consumers being more sensitive to higher prices after being informed. The study highlights the importance of informed consumer education in promoting environmentally sustainable products like wine from FRGVs.